Factors Associated With Metabolic Syndrome in a Mediterranean Population: Role of Caffeinated Beverages - Grosso, Giuseppe; Marventano, Stefano; Galvano, Fabio; Pajak, Andrzej; Mistretta, Antonio (Journal of epidemiology, 2014)
Intake of caffeinated beverages, such as coffee and tea, has been related to improvements in components of metabolic syndrome (MetS), but studies conducted in the Mediterranean region are scarce. The aim of this study was to evaluate whether or not consumption of a variety of beverages containing caffeine was associated with components of MetS in an Italian population. From May 2009 to December 2010, a cross-sectional survey was conducted on 1889 inhabitants living in Sicily, southern Italy. Data regarding demographic characteristics, habitual beverage intake, and adherence to the Mediterranean diet were collected, and clinical information was retrieved from the general practitioners' computer records. After adjusting for all covariates, coffee (odds ratio [OR] 0.43, 95% confidence interval [CI] 0.27-0.70) and tea (OR 0.51, 95% CI 0.34-0.78) were associated with MetS, whereas no association was observed between caffeine intake and MetS. Among other factors, age, body mass index, physical activity, current smoking, and adherence to Mediterranean diet were associated with having MetS. Triglycerides were inversely associated with consumption of both espresso coffee and tea. The healthy effects of such beverages were more evident in individuals with unhealthy dietary habits. Although no direct association between caffeine intake and MetS or its components was observed, coffee and tea consumption was significantly related to reduced odds of MetS.